FREQUENCY OF DIFFERENT CAUSES OF PAINFUL SWOLLEN LEG IN PATIENTS REFERRED FOR SONOGRAPHIC EXAMINATION AT A TEACHING HOSPITAL - Hadi, Noor Ul; Iqbal, Mohammad; Awan, Khursheed Hassan (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the frequency of different causes of painful swollen leg in patients referred for sonographic examination at a teaching hospital. Methodology: This was a descriptive study, carried out at the Department of Radiology, Lady Reading Hospital, Peshawar from April 2015 to September 2015. A total of 241 consecutive patients presenting with painful swollen lower limb from 23 to 85 years of age of both sexes referred to Department of Radiology for ultrasound were included in the study. Each of these patients underwent sonographic examination. Toshiba Nemio 20 Color / Power Doppler ultrasound machine having 7.5 MHz linear probe were used. Results: Out of 241 patients, 33.2% were male and 66.8% were female. Mean age of the patients was 58.09 years. The causes of painful swollen leg were DVT 51.9%, intramuscular abscess 12%, cellulitis 9.5% and ruptured baker's cyst in 8.7% of patients. Conclusion: Deep vein thrombosis is the commonest cause of painful swollen leg in our population.